2009
DOI: 10.1128/jvi.01630-08
|View full text |Cite
|
Sign up to set email alerts
|

Homodimerization of Marek's Disease Virus-Encoded Meq Protein Is Not Sufficient for Transformation of Lymphocytes in Chickens

Abstract: Marek's disease virus (MDV),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…dimerization abolish viral oncogenicity (Brown et al, 2006), suggesting that partnering with other bZIP proteins is important for Meq oncogenicity. Recent data have also shown that homodimerization alone is insufficient for Meq-induced transformation by MDV (Suchodolski et al, 2009). The N-terminal region of Meq contains a PLDLS motif, also present in other viral oncoproteins such as adenovirus E1A (Chinnadurai, 2002(Chinnadurai, , 2009) and EBV EBNA3A (Hickabottom et al, 2002), with which they interact with the transcriptional co-repressor C-terminal binding protein-1 (CtBP).…”
Section: Introductionmentioning
confidence: 99%
“…dimerization abolish viral oncogenicity (Brown et al, 2006), suggesting that partnering with other bZIP proteins is important for Meq oncogenicity. Recent data have also shown that homodimerization alone is insufficient for Meq-induced transformation by MDV (Suchodolski et al, 2009). The N-terminal region of Meq contains a PLDLS motif, also present in other viral oncoproteins such as adenovirus E1A (Chinnadurai, 2002(Chinnadurai, , 2009) and EBV EBNA3A (Hickabottom et al, 2002), with which they interact with the transcriptional co-repressor C-terminal binding protein-1 (CtBP).…”
Section: Introductionmentioning
confidence: 99%
“…The best candidate for an MDV protein involved in histone modification is Meq, since it is one of the few proteins expressed during latency, has a nuclear distribution, binds DNA, and regulates transcription (9,49,50). The ability to repress transcription as a homodimer probably relates to its ability to interact with the cellular corepressor CtBP (8), and this provides a potential link to the polycomb complexes responsible for H3K27me3 (46).…”
Section: Discussionmentioning
confidence: 99%
“…The only homodimer binding site that has been identified in the MDV genome is at OriLyt, but several MERE-1 (AP-1) sites are found in the latencyassociated region (27,34). Meq homo-and heterodimerization and Meq binding to the cellular corepressor CtBP are all required for its oncogenic activity (8,9,30,49,50).…”
mentioning
confidence: 99%
“…Both types of dimers are required for GaHV-2-induced T lymphomagenesis: the Meq/Meq homodimer as a transrepressor on MERE (MEq response element, ACACA) and the Meq/Jun heterodimer as a transactivator on the AP-1 RE (6,8,(50)(51)(52). The predicted MERE repressor site, which, unlike the MERE of the pp14/38 promoter (6), is located just downstream from the TSS (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that Meq can form either heterodimers with other bZIP proteins, such as c-Jun, that bind to AP-1-responsive elements (REs), such as CRE (TGACGTCA) or TRE (TGASTCA), or homodimers that bind to Meq-responsive element II (MEREII) (RA CACACAY) and with a lower affinity to MEREI (GAGTGATGA CGTCATC) (5,6). The transactivation properties of Meq depend on its dimerization partner: Meq/Meq homodimers repress expression of the pp24/38 gene by binding to a MEREII site (6), whereas Jun/Meq heterodimers transactivate the expression of ICP4 and meq by binding to AP-1 REs (6)(7)(8). Meq may also regulate cellular genes, such as those for interleukin-2 (IL-2) (6), CD30 (1), and Bcl-2 (7), and may increase the transcription of genes involved in growth and antiapoptotic pathways, such as the Jun pathways, during the induction of MD virus (MDV) lymphomagenesis (9).…”
mentioning
confidence: 99%